Weed management in upland rice (Oryza sativa L.) intercropped in coconut - Ravikiran (Department of Agronomy, College of Agriculture, 2018)
The investigation entitled “Weed management in upland rice (Oryza sativa L.) intercropped in coconut” was undertaken during the period, 2017 - 2018 at College of Agriculture, Vellayani, Thiruvananthapuram to standardise an eco-friendly and economic weed management strategy for upland rice intercropped in coconut. The field experiment was carried out at Coconut Research Station, Balaramapuram, Thiruvananthapuram district during the period from June to October 2017. The variety used was Prathyasa (MO-21) released from Rice Research Station, Moncompu. The experiment was laid out in randomized block design (factorial) with sixteen treatment combinations and three replications. The treatments consisted of two stale seedbed methods viz., stale seedbed with mechanical removal of weeds (s1) and no stale seedbed (s2) and eight weed management methods i.e., penoxsulam @ 20 g ha-1 at 10-15 days after sowing (DAS) fb hand weeding (HW) at 35-40 DAS (m1), penoxsulam @ 25 g ha-1 at 10-15 DAS fb HW at 35-40 DAS (m2), penoxsulam @ 30 g ha-1 at 10-15 DAS fb HW at 35-40 DAS (m3), penoxsulam @ 20 g ha-1 at 10-15 DAS fb metsulfuron methyl + chlorimuron ethyl (MM+CE) @ 4 g ha-1 at 35-40 DAS (m4), penoxsulam @ 25 g ha-1 at 10-15 DAS fb MM+CE @ 4 g ha-1 at 35-40 DAS (m5), penoxsulam @ 30 g ha-1 at 10-15 DAS fb MM+CE @ 4 g ha-1 at 35-40 DAS (m6), HW twice at 15 and 35 DAS (m7) and weedy check (m8). Study of the weed flora of experimental area indicated the dominance of broad leaved weeds (eight spp.) followed by grasses (six spp.) and sedges (two spp.). Stale seedbed method (s1) recorded significantly lower weed density at all stages of observations (15, 30 and 60 DAS), weed dry weight at 15 and 30 DAS and higher weed control efficiency (WCE) at 30 and 60 DAS compared to no stale seedbed. Among the weed management methods, at 60 DAS, all the penoxsulam doses i.e., 20, 25 and 30 g ha-1 at 10-15 DAS fb either HW at 35-40 DAS or MM+CE at 35-40 DAS (m 6, m4, m3, m5, m1 and m2) were on par in their effect on total weed dry weight and WCE. Stale seedbed method (s1) registered significantly higher plant height at 60 DAS, number of tillers m-2 at 30 DAS and at harvest, dry matter production at harvest and LAI at 60 DAS compared to no stale seedbed (s2). Penoxsulam at different doses fb HW treatments (m 1, m2 and m3) recorded higher plant height at 30 and 60 DAS and at harvest, number of tillers m-2 at 30 DAS, DMP at harvest and LAI at 30 DAS. None of the herbicide treated plots showed any phytotoxicity symptom on rice crop. The yield attributes viz., number of spikelets panicle-1, per cent filled grains and thousand grain weight were significantly higher for stale seedbed, compared to no stale seedbed (s2). Weed management methods also significantly improved yield attributes viz., panilces m-2, spikelets panicles-1, per cent filled grains and thousand grain weight compared to weedy check treatment. Penoxsulam @ 25 g ha-1 at 10-15 DAS fb HW at 35-40 DAS (m2) registered the highest values for per cent filled grains and thousand grain weight. Stale seedbed method (s1) recorded significantly higher grain yield, straw yield and lower weed index compared to no stale seedbed method (s 2). Though penoxsulam @ 25 g ha-1 at 10-15 DAS fb HW at 35-40 DAS (m2) registered the highest grain yield (3.23 t ha-1), it was on par with the other penoxsulam fb HW treatments viz., m1 and m3. None of the s x m interactions were found statistically significant. Regarding weed index also m2 registered the lowest value and it was significantly superior to all other weed management methods. Higher net income (₹ 27, 848/-) and B:C ratio (1.48) were obtained with stale seedbed method (s1), compared to no stale seedbed (s2). Application of penoxsulam @ 25 g ha-1 at 10-15 DAS fb HW at 35-40 DAS (m2) registered the highest net income (₹ 36,090/-) and B: C ratio (1.63). The s1m2 registered the highest net income (₹ 44,433/-) and B: C ratio (1.77), among the interactions. The results on soil microbial population revealed that population of fungi, bacteria and actinomycetes increased in all the herbicidal treatments compared to pre-treatment population. Activity of dehydrogenase enzyme also increased significantly in the herbicide applied plots implying the safety of the tested chemicals on soil health. Based on grain yield, weed index and economic analysis, integration of stale seedbed method with the broad spectrum herbicide penoxsulam @ 25 g ha-1 at 10-15 DAS fb HW at 35-40 DAS can be recommended as an eco-friendly and economic weed management practice in upland rice.